Pelatihan Installasi E-Learning Sebagai Media Pembelajaran Daring Menggunakan MLS Moodle Aplikasi - Zamzami Zamzami; Didik Siswanto; Muhammad Sadar (Asosiasi Dosen Akuntansi Indonesia, 2021)
At the gold page foundation, Riau rose to have many levels of education under it, such as the Lukman Edi Islamic College (STAILe), formal education under the tertiary level as well as MTS (Madrasah Tsanawiyah) and MA (Madrasah Aliah). A pandemic like this has disturbed all business and business sectors, as well as an impact on the world of education. Many now the learning system and lecture system are turning online because they follow the health protocols that have been announced by the government. The discourse from the government is the basis for the emergence of this proposal. The plague that we do not know how long it will run out has made learning methods and systems change 180 degrees. Moodle is a name for an application program that can transform a learning medium into a web form. MOODLE is provided free of charge as open source software under the GNU Public License, which means that even though it has copyright, MOODLE still provides the freedom for users to duplicate, use it and modify it. MOODLE stands for Modular Object Oriented Dynamic Learning Environment, which is basically teaching and students doing teaching activities in online training. MOODLE (Modular Object Oriented Dynamic Learning Environment) is designed using pedagogical principles to help education create an effective E-Learning system. This application allows users to enter the